Green synthesis of Eosin-Y coated silver nanoparticles for sensitive and selective fluorometric detection of L-Dopa - Nagaraj, Karuppiah; Thangamuniyandi, P.; Velmurugan, Gunasekaran; Alotaibi, Khalid M.; Raja, K.; Sharma, Bhuwanesh K. (Journal of fluorescence, 2025)
This study is to produce biogenic silver nanoparticles (AgNPs) by utilizing aqueous extracts derived from Turnera Sublata (TS) leaves under visible light. Subsequently, these nanoparticles are coated with eosin-yellow (EY) to enhance sensitivity and selectivity in L-3,4-dihydroxyphenylalanine (L-dopa) detection. This method encompasses the deposition of metal onto the Ag NPs, resulting in the formation of EY-AgNPs. The crystalline, spherical nanoparticles, prepared as described, exhibit a particle size of 20 nm. Different instruments were used to characterize them, including UV-Vis spectroscopy, fluorescence spectroscopy, FTIR spectroscopy, selected area electron diffraction (SAED), transmission electron microscopy (TEM), and X-ray diffraction (XRD) analysis. The spherical structured morphology and size of the EY-AgNPs has been confirmed through SAED and TEM studies. This study pioneered the integration of characteristic hydroxyl-Ag chemistry and specialized steric interference of organic pigment in luminescent AgNPs to develop a simple method for detecting dopa. The sensor’s dynamic range and limit of detection were assessed. Experimental results revealed that green-emitting AgNPs shielded by interference from biogenic AgNPs and the strong affinity of hydroxyl-silver provided a high-sensitivity detection limit of 1.84 nM. Furthermore, a new green approach for sensor development using human serum albumin (HSA) assay demonstrated that organic dye on the surface of nanomaterials further enhances sensing properties.
Gesehen am 19.09.2025